Designing Interactive Multimedia Computer Graphics Using The 4D Method as Self-Directed Learning for Students - Rusyada, Gozin Najah; Switrayana, I Nyoman; Mahfuzi Ardiyati, Syafira (Indo-MathEdu Intellectuals Journal, 2023)
The process of Self-directed learning of students using modules or consulting by asking for online explana-tions to lecturers is still not effective, especially for Computer Graphics courses that prioritize psychomotor aspects, namely skills. This research aims to develop learning media in the form of interactive multimedia to support Self-directed learning of Computer Graphics course students. This research uses the type of develop-ment research or Research and Development. The development procedure used adopted Thiagarajan's 4D model. This research produces multimedia products consisting of an initial page, the main menu page includes introduction, material, developer profile and quiz or evaluation. The multimedia developed effectively improves student learning outcomes through Self-directed learning in terms of an increase in the average score of pre-test and post-test results from 67.22 to 82.41, which means that there is an increase in student learning out-comes by 15.19%.